Analisis Persepsi Peserta Didik dan Guru Terhadap Kebermaknaan Praktikum IPA Di SMP Kota Pontianak - Amalia Pradana, Nia; Nurdini Mardiyyaningsih, Asriah; Ariyati, Eka (PendIPA Journal of Science Education, 2026)
The implementation of science practicums in junior high schools should support meaningful learning. However, in reality, they are often considered merely a supplement to theory. This study aims to compare the perceptions of students and teachers regarding the meaningfulness of science practicums in junior high schools in Pontianak City. The research was conducted using a survey method with a closed-ended questionnaire, the Meaningful Learning in the Laboratory Instrument (MLLI), which had been modified for use at the junior high school level. There were four indicators in accordance with the MLLI, namely motivation, critical thinking, procedural skills, and the benefits of practical work. Samples were randomly selected from 12 junior high schools that granted permission for the research. The results showed that students rated the meaningfulness of practical work at an average of 74% (in the high category), while teachers rated the meaningfulness of practical work at an average of 79% (in the very high category). The indicator of practical benefits received the highest score, while the indicators of critical thinking and skills were still low. These findings suggest that practical work has provided valuable learning experiences, but requires optimization through a more intensive inquiry and guidance approach to further develop students' critical thinking skills.